Investigating the Anti-epileptic and Sedative Effects of Hydroalcoholic Extract of Melissa officinalis (Lemon Balm) Leaf on Pentylenetetrazol Induced Epileptiform Seizures in Wistar Rat - MB Ghayour; M Behnam-Rassouli; N Ghayour; M Tehranipour; A Kamyabi-Abkooh (Institue of Medicinal Plants, ACECR, 2012)
Background: Since long lasting administration of anti-seizure drugs produces undesirable side effects, many efforts have been made during recent decades to find and replace the chemical drugs by medicinal plants.   Objective: The aim of present study was to study the antiepileptic (anti-seizure) effects of hydroalcoholic extract of Melissa officinalis on experimental epileptiform seizures, induced by pentylenetetrazol (PTZ) in Wistar rat.   Methods: After normalization, rats in experimental groups 1, 2 and 3 were injected (i.p) 50, 80 and 120 mg/kg hydroalcoholic extract of Melissa officinalis , respectively. Control animals were injected extract solvent as the same manner. After 30 minutes all rats were injected (i.p) 80 mg/kg PTZ and then examined for epileptiform behaviors for the next 60 minutes. The rate of mortality during the next 24 hour was also recorded.   Results: In comparison with control group, in all experimental groups the latent period of tonic-clonic generalized seizure was significantly (P<0.05) increased. Moreover, the mortality rate was decreased from 90% in control group to 30, 50 and 60% in experimental groups 1, 2 and 3, respectively. Conclusions: I t can be concluded that hydroalcoholic extract of Melissa officinalis has potential sedative and anticonvulsant effects and probably exerts its effects through GABAergic system.